Simplified methods for local correction of system international normalized ratio - سعيد روز; عباس نورما (Latakia University Journal -Medical Sciences Series, 2022)
Background: The Prothrombin Time (PT) assay is the most common test performed in hemostasis laboratories, often converted to an international normalized ratio (INR) to monitor anticoagulant therapy using vitamin K antagonists (VKAs), such as warfarin. Although the INR is meant to standardize PT values by taking into consideration the reagent and instrument variability; substantial inter-laboratory variation in INRs still exists and suggests that this can be further improved. This paper describes two methods of INR correction, one (Favaloro method) based on improving the accuracy of the main components of the INR (MNPT/ISI), using normal and pathological samples from VKA-stabilized patients, and the other (Chandrshekar method) aims to bypass the ISI and finds a direct relationship between the INR and PT, using normal and pathological random samples that are not limited to patients stabilized on VKAs, i.e., prolonged PT samples are used regardless of the causal diagnosis Purpose: A practical comparison of two simplified methods of local correction of the international normalized ratio (INR) applicable in Tishreen University Hospital. Methods: The final study sample included 700 patients, 550 had a prolonged PT and 150 had a normal PT. Some of the latter was used to apply the methods used in this research, and the remaining section was used to calculate the MNPT for the various reagents, Results: In both methods, the difference between INRs i.e. (observed INR – corrected INR) decreased by increasing the number of samples (a more accurate correction for INR). By comparing the two methods, we found that the difference between the INRs was less using Chandrshekar method than using Favaloro method with statistical significance, indicating that, the Chandrshekar method is more accurate and easier to correct. We also noted that changing the material from the device company leads to significant differences between the INRs that requires correction. Conclusion: Two methods are applicable in a large medical center such as Tishreen University Hospital, so that the appropriate method is chosen as per the working conditions according to the available capabilities of the used reagents and devices